Analisis Pengaruh Pembiayaan Istishna, Qardh dan Ijarah Terhadap Return on Asset Pada PT Bank Bri Syariah Tbk - Salma Aulia Devyane; Kristianingsih Kristianingsih; Endang Hatma Juniwati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study discusses the impact of Istishna financing, Qardh financing and Ijarah financing on the return on assets (ROA) of PT Bank Bri Syariah Tbk. affects the increase at bank income, but the data seen is not in accordance with the theory. The question raised by this research is whether Istishna financing, Qardh financing, and Ijarah financing have a partial and simultaneous impact on the return on assets (ROA). The purpose of this research is to understand the effect of Istishna's financing, and Ijarah financing having an effect on Return On Asset (ROA) partially and simultaneously at PT Bank Bri Syariah Tbk. This study is a quantitative study using second-hand data, with a sample size of 36 samples. The mandatory data technique is documentation, namely PT Bank Bri Syariah Tbk financial ratio report data published by the Financial Services Authority through the OJK website and the Bank Bri Syariah website. This study is a quantitative study using second-hand data, with a sample size of 36 samples. Data analysis techniques use classical hypothesis testing and multiple linear regression, and use SPSS version 25 tools to process the data. , qardh and ijarah return on financing assets (ROA), can be concluded from the results of the regression test, if F test with a significant level value is the output table is 0.032. This means the Significant Value <0.05. This means there is an influence between istishna, qardh and ijarah on ROA of Bank BRI Syariah Indonesia simultaneously (together).